CHALLENGES IN IMPLEMENTING PREPOSITIONS OF TIME, PLACE AND DIRECTION FOR FIRST SEMESTER STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Imelda Woa Wene; Arima Renny Dayu Putri (ELTR Journal, 2018)
This study examined the English proficiency of English Language Education Study Program students, with main focus the use of prepositions of time, place and direction. The researchers discussed the difficulties of first semester students in using these prepositions properly in the sentences. The participants of this research were the first semester students of English Language Education Study Program at Sanata Dharma University. The researchers invited 43 students in the DPA class. The data of this research were collected from questionnaires and Cloze Tests. The collected data from questionnaires were analyzed based on Likert Scale. The data resulted from Cloze Tests were concluded using Level of Achievement Score. The results confirmed that the students experienced the difficulties in using the preposition of place and direction than the preposition of time. The findings revealed that the students were confused in the use of words in, on, and toward. Furthermore, the findings imply that the students should pay more attention to the prepositions and need to find the best strategies to acquire them.